Impact of Entrepreneurial Characteristics and Access to Credit on Business Performance of Small Business (Case: Brown Sugar Processing in Agam District) - Nadia Firnalista; Nofialdi; Zednita Azriani (Indonesian Journal of Agricultural Research, 2020)
Small businesses' performance needs to be improved because it plays an essential role in driving economic growth and development. This study focuses on examining the effect of entrepreneurial characteristics on small business performance. Data was collected through a survey by giving questionnaires to 100 small business entrepreneurs processing brown sugar. Structural Equation Model (SEM) was chosen to ensure the relationship between variables. Empirical findings indicate that entrepreneurial characteristics affect business performance directly and indirectly through credit access, entrepreneurial characteristics affect credit access, and credit access affects business performance. Business performance improvement of brown sugar entrepreneurs needs government assistance and building networks.